Corporate Governance and Institutional Ownership - Chung, Kee H.; Zhang, Hao (Journal of Financial and Quantitative Analysis, 2011)
Abstract In this study we examine the relation between corporate governance and institutional ownership. Our empirical results show that the fraction of a company’s shares that are held by institutional investors increases with the quality of its governance structure. In a similar vein, we show that the proportion of institutions that hold a firm’s shares increases with its governance quality. Our results are robust to different estimation methods and alternative model specifications. These results are consistent with the conjecture that institutional investors gravitate to stocks of companies with good governance structure to meet fiduciary responsibility as well as to minimize monitoring and exit costs.